Collaborative Networks, Decision Systems, Web Applications and Services for Supporting Engineering and Production Management - Varela, Leonilde; Putnik, Goran D. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focused on fundamental and applied research on collaborative and intelligent networks and decision systems and services for supporting engineering and production management, along with other kinds of problems and services. The development and application of innovative collaborative approaches and systems are of primer importance currently, in Industry 4.0. Special attention is given to flexible and cyber-physical systems, and advanced design, manufacturing and management, based on artificial intelligence approaches and practices, among others, including social systems and services.